STUDI TENTANG TINGKAT KESEGARAN JASMANI SISWA PUTRA KELAS V SDN 015 JAKE KUANTAN TENGAH - Pendriyon, Pendriyon; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract, Based on a review on the ground that has been done, that the Student Class V SDN 015 Jake Kuantan Tengah majority of students have no visible physical fitness is good, it looks and a lack of student learning by not following the lesson seriously, was absent due to illness and also the lack of student motivation in following the separation-day learning activities in schools. This makes researchers are interested to know the level of physical fitness of students of SDN 015 Jake to conduct a research on the study of physical fitness level of students of SDN 015 Jake Kuantan Tengah. This type of research is descriptive according Sugiyono (2005: 11) that the descriptive research is research conducted to determine the value of an independent variable, either one or more variables (independent) without making comparisons, or connect between one variable with another variable. The sample was 015 students of class V SDN totaling 31 people with a total sampling technique. Data obtained from the tests TKJI consisting of five test items. Analyzed using deskriptf and norms based on the physical fitness level. Having analyzed it was found that: For Physical fitness level of students of SDN 015 Jake Kuantan Tengah by category excellent, good, sufficient and are no .. To Level Physical Freshness graders of SDN 015 Jake Kuantan Tengah category poor results obtained 25.81% the number of students as many as 8 people. For Level Physical Freshness graders of SDN 015 Jake Kuantan Tengah with less category once showed 74.91% the number of students as many as 23 people.Keywords: Physical Fitness